Pandangan Abraham Maslow tentang Memanusiakan Manusia untuk Pemaknaan pada Era Modern di Indonesia - Siti Latifah Agistiani (Gunung Djati Conference Series, 2023)
This study aims to discuss Abraham Maslow's views on humanizing humans for meaning in the modern era in Indonesia. This study uses a qualitative approach by applying the method descriptive-analytical. The formal object of this research is the view of Abraham Maslow, while the material object is humanizing humans. The scope of research is in the modern era. The rest, the context of this research is in Indonesia. The results and discussion in this study indicate that education is the beginning of the formation of a child's character with the aim of humanizing humans. Education in Indonesia has also initiated an independent learning program "strengthening character education" and the same is true of Abraham Maslow's theory of humanism where education frees up a student to be more creative with the aim of being able to bring out his creativity or talent within himself. This research concludes thatAbraham Maslow's views on humanizing humans for meaning in the modern era in Indonesia have been successfully applied to their education and Indonesia has been named the world's most friendly countries based on the Expat Insider 2022 survey version of Internations Indonesia occupies second place after Mexico. This happens from a smile, mutual respect, and respect amidst the differences and shortcomings that exist. This study recommends that the institutions and organizations of education and social services for the community always strengthen the attitude of humanizing humans in Indonesia.